Research Trend and Productivity of the Qur’anic Physics Research Based on Scopus Database (1992-2020) - Alfany, Selsy Florensia; Arrizkiyah, Alisa; Suprapto, Nadi; Deta, Utama Alan (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2022)
This study has aimed to analyze the development of physics context research in the Qur'an using bibliometric techniques from 1992 to 2020 with the Scopus database. The data accounted for 187 documents. The results showed fluctuating numbers in researching qur'anic physics. However, the trend was increased from 2016 to 2020. Indonesia is one of the countries that contributes the most research on qur'anic physics even though the language used in all documents was in English. The Institute of Physics (IOP) Publishing dominated publishers' research on qur'anic physics. The top author in this domain was Adiwijaya, who dominated in 2018-2020. Based on the VOSviewer visualization, the whole research resulted in two clusters. The first cluster was related to Islam. The second cluster dealt with systems in relating to qur’anic physics. Thus, this research was targeted to determine the research development of qur'anic physics and help the future research.